Actividad biológicas de los extractos obtenidos a partir de tubérculos andinos - Cantos Jiménez, Mélany Germania (2022)
ABSTRACT: Within the knowledge of ancestral medicine, the use of plants with medicinal qualities to prevent certain health disorders stands out. Plant species have anti-inflammatory, antioxidant, and anticancer properties, among others; for which non-essential substances or biological compounds are responsible. Their study has increased at present, since these molecules have biological activity. When evidencing a small number of investigations about tubers in this context, which are consumed and produced in the Andean region, it was decided to determine the biological activity from extracts of mashua (Tropaeolum tuberosum) and melloco (Ullucus tuberosus). in the city of Riobamba. Obtaining as a result the presence of hemagglutinating activity when evaluating the aqueous extract of T. tuberosum that was able to specifically agglutinate the red blood cells of blood group A. The anticoagulant activity was evidenced in the aqueous extracts obtained from mashua and melloco, which inhibited the activity of blood coagulation proteins of the intrinsic pathway evidenced by the prolongation of activated Thromboplastin Time (aPTT). Additionally, the antibacterial and antifungal activity was verified by evaluating the aqueous and ethanolic extracts obtained from the mentioned tubers, highlighting their inhibition action on the growth of ATCC gram-positive bacterial strains Staphylococcus aureus, Enterococcus faecalis and gram-negative Escherichia coli, Klebsiella pneumoniae. and Proteus mirabilis, as well as yeasts of the genus Candida: C. albicans, C. krusei, C. glabrata and C. tropicalis. Keywords: Biological Activity, Hemagglutination, Anticoagulation, Antibacterial, Antimycotic, Tropaeolum tuberosum and Ullucus tuberosus